Migration Policy as a Challenging European Policy - Myrotis, Panagiotis (HAPSc Policy Briefs Series, 2023)
Since 2014 a new policy topic has appeared and integrated in national and European political agenda, the migration crisis. The migration crisis, that peaked in 2015 had as a result, not only the movement of a large number of migrants to Europe, but also created friction and new conflicts between member states of the European Union. The aim of this paper is to focus on the current situation of the topic of European migration policy and to highlight the issues that arise from migration. In conclusion, attempts to propose some actions in order to manage this multidimensional phenomenon will be analyzed. The attempt to reach this aim is done via the study of primary sources such as decisions of European Union and statistics from international organizations, as well as secondary sources such as relevant analyses and studies.